Assessment of the pattern of SS1 students pre-level mathematics cognitive and content achievement (2018)
This study investigates cognitive and content pattern of SS1students' pre-level Mathematics achievement. The study also investigated gender role on the pattern of cognitive and content of SS1 pre-level mathematics achievement. A total of 355participants were drawn from six public secondary schools across two randomly selected local governments in Ibadan Metropolis in Oyo State. The instrument has a reliability of 0.74. Three research questions were answered. Results obtained indicated that SS1 students demonstrated highest strength in geometry and mensuration ( x = 46.45) algebraic processes ( x = 37.05), statistics and probabilities ( x = 33.27) are the contents that students are still finding most difficult Students performed poorly on questions that required higher order thinking ( x = 40.04) but found questions that tested recall ability quite easy ( x = 45.35). The way both male and female SS1 students performed based on content and levels of cognition does not differ significantly al 0.05 level of significance. Teachers should explore the findings to identify areas of mathematics that demand more efforts for improved performance